2015
DOI: 10.1088/2040-8978/17/10/105804
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneously integrated optical detection platform for on-chip sensing applications

Abstract: This paper introduces a resonant waveguide grating (RWG) integrated with a photodetector for on-chip sensing applications. An inverted thin film indium gallium arsenide (InGaAs) metal–semiconductor–metal photodetector is heterogeneously integrated on silicon dioxide (SiO2)/ silicon substrate using fluidic self-assembly. The inverted optical waveguide and the RWG structure are subsequently fabricated utilizing layer-by-layer post-processing techniques. Detailed electrical, optical, and optoelectronic characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It has been demonstrated in massively parallel microassembly of semiconductor chips [10], [11] achieving sub-micron precision at great throughput and high yield [12]. Capillary selfalignment has also been used for integrating 3D microstructures, [12]- [15] GaAs blocks [16] and optoelectronic devices [17]. A comprehensive review of capillary self-alignment can be found at [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated in massively parallel microassembly of semiconductor chips [10], [11] achieving sub-micron precision at great throughput and high yield [12]. Capillary selfalignment has also been used for integrating 3D microstructures, [12]- [15] GaAs blocks [16] and optoelectronic devices [17]. A comprehensive review of capillary self-alignment can be found at [18].…”
Section: Introductionmentioning
confidence: 99%